Kualitas Tidur Mahasiswa Farmasi: Dampak Stres Akademik dan Efikasi Diri Saat Skripsi - Gita Fitria Maharani; Nia Anggri Noveni; Nur’Aeni .; Dyah Astorini Wulandari (Psychopolytan : Jurnal Psikologi, 2024)
Pharmacy students who are working on their thesis experience impacts on physical and psychological health such as experiencing poor sleep quality. Poor sleep quality can trigger academic stress and is supported by low self-efficacy. Therefore, the lower the quality of sleep possessed by students, the higher the level of academic stress in completing the thesis and vice versa. The purpose of this study was to examine the effect of academic stress and self-efficacy on sleep quality in 2020 Faculty of Pharmacy students at Muhammadiyah Purwokerto University who are doing thesis. This study uses quantitative methods with multiple linear regression tests. Respondents in this study totalled 101 Faculty of Pharmacy students. The measuring instruments used were sleep quality scale, academic stress scale, and self-efficacy scale. The results showed that academic stress and self-efficacy can simultaneously contribute an influence of 31.5% on sleep quality. Efforts are needed to improve sleep quality in order to minimize academic stress, such as practicing self-control to boost confidence in completing their thesis.